2006
DOI: 10.1136/jnnp.2006.099333
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of a home based exercise programme to reduce the risk of falling among people with Parkinson's disease

Abstract: Objective: To evaluate the effectiveness of a personalised home programme of exercises and strategies for repeat fallers with Parkinson's disease (PD). Method: Patients with a confirmed diagnosis of idiopathic PD, independently mobile, living at home in the community, experiencing more than one fall in the previous 12 months and with intact gross cognitive function were invited to participate in this randomised controlled trial. Usual care was compared with a personalised 6 week, home based exercise and strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
332
3
23

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(373 citation statements)
references
References 29 publications
15
332
3
23
Order By: Relevance
“…In line with our findings, which showed that 8 weeks of ABCT caused no significant difference in FOF, FOG, and risk of fall in PD patients, the results of a study by Allen (2011) showed that low-intensity exercises had no effects on fall prevention (57). Ashburn et al (2007) also showed that a 6-week, home-based protocol caused no changes in the risk of falling in a 6-month period (62). As previously reported, a 6-month history of fall can be regarded as a valid criterion for posture instability (63).…”
Section: Discussionsupporting
confidence: 78%
“…In line with our findings, which showed that 8 weeks of ABCT caused no significant difference in FOF, FOG, and risk of fall in PD patients, the results of a study by Allen (2011) showed that low-intensity exercises had no effects on fall prevention (57). Ashburn et al (2007) also showed that a 6-week, home-based protocol caused no changes in the risk of falling in a 6-month period (62). As previously reported, a 6-month history of fall can be regarded as a valid criterion for posture instability (63).…”
Section: Discussionsupporting
confidence: 78%
“…Specific areas of change included physical activity, spiritual growth, and stress management. Ashburn et al reported on an RCT of a home-based exercise program to reduce falling in the population with Parkinson disease [26]. Participants were recruited from two National Health Service trusts in Dorset, United Kingdom, with well-defined inclusion and exclusion criteria.…”
Section: IVmentioning
confidence: 99%
“…(placebo) 78 Ashburn 238 showed a non-significant trend towards a reduction in falls in patients with…”
Section: Tai Chimentioning
confidence: 99%